Tinjauan Hukum Pidana dan Hukum Islam tentang Kejahatan Aborsi - Asrianto Zainal (Al-'Adl, 2016)
This study entitled "A review of criminal law and Islamic law on the crime of abortion (a comparative study). The main issue to be discussed in this thesis is "Is abortion as a crime by reason of an emergency can be used as a common criminal deletion / Islam and How comparative criminal law and Islamic law against the crime of abortion"? in order to determine the concepts offered between criminal law and Islamic law in view of the phenomenon of abortion crimes committed by people who are not responsible or with a specific reason. In this study, the authors used a qualitative study using descriptive analysis that describes the issues to be studied. And the collection of data in this thesis done in literature. Namely, by collecting data obtained from literature sources such as books, legislation, magazines and newspapers. The data have been collected and inventoried and further grouped or classified according to the materials and problems. From the results of research conducted by the authors find that abortion is justified by the positive law and the law of Islam is the act of abortion is performed when the pregnancy could endanger the lives of pregnant women and fetuses, thepermissibility of abortion must refer to the provisions of the medical, so that in practice does not mebawa even worse consequences for the mother, and especially in Islamic law should be referred to the shar'i predetermined While abortion is a criminal act (abortion provokatus criminalis) is an act of abortions performed for no apparent reason, for example, the fear of poverty or fear of pregnancy is a disgrace. Islamic law and positive law equally see it as a crime (criminal offense), so as to provide penalties for those who do.